Oseltamivir and influenza-related complications in children: a retrospective cohort in primary care. Issue 5 (12th November 2020) - Lee, Joseph Jonathan; Smith, Margaret; Bankhead, Clare; Perera Salazar, Rafael; Kousoulis, Antonis A.; Butler, Christopher C.; Wang, Kay
Background: Influenza and influenza-like illness (ILI) place considerable burden on healthcare systems, especially during influenza epidemics and pandemics. During the 2009/10 H1N1 influenza pandemic, UK national guidelines recommended antiviral medications for patients presenting within 72 h of ILI onset. However, it is not clear whether antiviral treatment was associated with reductions in influenza-related complications. Methods: Our study population consisted of a retrospective cohort of children aged ≤17 years who presented with influenza/ILI at UK primary care practices contributing to the Clinical Practice Research Datalink during the 2009/10 pandemic. We used doubly robust inverse-probability weighted propensity scores and physician prior prescribing instrumental variable methods to estimate the causal effect of oseltamivir prescribing on influenza-related complications. Secondary outcomes were complications requiring intervention, pneumonia, pneumonia or hospitalisation, influenza-related hospitalisation and all-cause hospitalisation. Results: We included 16 162 children, of whom 4028 (24.9%) were prescribed oseltamivir, and 753 (4.7%) had recorded complications. Under propensity score analyses oseltamivir prescriptions were associated with reduced influenza-related complications (risk difference (RD) −0.015, 95% CI −0.022–−0.008), complications requiring further intervention, pneumonia, pneumonia or hospitalisation and influenza-related hospitalisation, but not all-cause hospitalisation. Adjusted instrumental variable analyses estimated reduced influenza-related complications (RD −0.032, 95% CI −0.051–−0.013), pneumonia or hospitalisation, all-cause and influenza-related hospitalisations. Conclusions: Based on causal inference analyses of observational data, oseltamivir treatment in children with influenza/ILI was associated with a small but statistically significant reduction in influenza-related complications during an influenza pandemic. Children with influenza-like illness during the 2009–2010 influenza pandemic experienced fewer complications when prescribed oseltamivir https://bit.ly/2TJcej4